Money, oil, and empire in the Middle East : sterling and postwar imperialism, 1944-1971 - Galpern, Steven G., 1969- (Cambridge, UK ; New York : Cambridge University Press, 2009)
"An important new political and economic history of the unravelling of the British Empire and its connection to the decline of sterling as a leading international currency. Analyzing events such as the 1951 Ira nian oil nationalization crisis and the 1956 Suez crisis, Steven Galper n provides a new perspective on British imperialism in the Middle East by reframing British policy in the context of the government's postwar efforts to maintain the international prestige of the pound. He reveals the link that British officials made between the Middle Eastern oil tr ade and the strength of sterling and how this influenced government pol icy and strained relationships with the Middle East, the United States, and multinational oil firms. In so doing, this book draws revealing pa rallels between the British experience and that of the United States to day and will be essential reading for scholars of the British empire, M iddle East studies and economic history"--Provided by publisher.
Anglo-American conflict over oil and the sterling area -- Sterling a nd Britain's confrontation with nationalism in Iran -- The Suez crisis : a sterling rescue operation gone wrong -- Kuwait's surplus oil revenu e : the benefit and threat to sterling -- Conclusion : the devaluation of 1967 and the end of empire.
Includes bibliographical references and index.
Keywords: Petroleum industry and trade -- Great Britain -- History -- 20th cen tury; Petroleum industry and trade -- Middle East -- History -- 20th centu ry; Pound, British -- History -- 20th century; Imperialism -- History -- 20th century